STUDY OF SOLAR POWER PLANT (SPP) WITH 1.51 MWP CAPACITY AT TANJUNGPURA UNIVERSITY - Ridwan, Muhammad Daflie; Hiendro, Ayong; Fitriah, Fitriah (Faculty of Engineering, Universitas Tanjungpura, 2023)
This research aims to optimize solar power generation at Tanjungpura University's Bralian Merdeka Yanuar Building by harnessing solar energy as a renewable resource. Indonesia, being near the equator with abundant solar radiation, holds significant potential for solar energy utilization. The main goal is to design and implement a 1.51 MWp capacity Solar Power Plant at the building to reduce reliance on fossil fuels and minimize carbon emissions on campus. The study utilizes a descriptive-analytical method, conducting literature reviews, site surveys, and electricity generation calculations using PVSyst software. Solar radiation data, electricity consumption, and building energy requirements guide the analysis. The SPP, comprising 2800 solar panels and 12 inverters, can effectively meet the Bralian Merdeka Yanuar Building's electricity needs. This research highlights solar energy's potential as a renewable resource to reduce carbon emissions and enhance energy independence. Successful SPP implementation serves as an alternative to fulfill the building's electricity demands, The azimuth and tilt angles significantly influence the electricity production of the Photovoltaic Solar Power Plant built to meet the electricity needs of the building. The study deepens understanding of solar energy potential and its benefits in electricity generation for Indonesia.